HIGH-SPEEP ROLLING BEARING-DUAL ROTOR SPINDLE SYSTEM NUMERICAL SIMULATION ANALYSIS OF DISCRETE MODELING DYNAMICS - LI YunLong; TANG ZhiYu (Jixie qiangdu)
Based on the bearing dynamics and rotor dynamics models,the dynamic characteristics of aero-engine rolling bearing-dual rotor spindle system are studied. According to Timoshenko beam-axis theory,the finite element discretization model of rolling bearing-dual rotor spindle system is established and the numerical method is used to solve the problem. The results shows that:（ 1） Due to the influence of nonlinear characteristics of the system,the system responds to multiples and combined frequencies of the excitation frequency under multi-frequency coupling excitation,the system vibration response is extremely complex.（ 2） The change of the radial clearance of the intermediate roller bearing has a certain influence on the system response,the effect on the response of the supporting bearing is small,and the small clearance can reduce the response displacement of the center of the intermediate bearing and the rotor system,so that the system tends to be stable.（ 3） Properly increasing the number of supporting bearing rolling elements reduces the response of the supporting bearing and rotor center,and the system stability also increases.（ 4） The general trend of the simulation curve is the same as the experimental data but not fully in agreement,and the result has some errors（ the error is about 15. 6%）. The analytic results will provide a referenced gist for the dynamic stability of dual-rotor-rolling-bearing by the quantitative and qualitative analysis.